(untitled) (MAUSAM, 1973)
Results of a climatological study of radar echoes around Nagpur for the non-monsoon months (October to May) based on data from 1960 to 1969 have been presented in this paper. The average distribution pattern reveal preponderance in echo formations in the eastern sectors. Echoes developing in northwest quadrant are believed to drift towards east during night or early morning hours.